Suboptimal sleep duration and circadian phenotype in adult women residents of Valencia, Venezuela, treated in health campaigns: An associated cardiometabolic profile - Ruiz-Fernández, Nelina (2019)
Objective: To evaluate the sleep duration, the circadian phenotypes, and their association with sociodemographic and clinical variables, lifestyle, and indicators of cardiometabolic risk in adult women. Materials and methods: A cross-sectional study of 108 adult women living in the city of Valencia, Venezuela, who were treated in health campaigns. Sociodemographic and clinical variables, lifestyle, self-reported sleep duration during weekdays and weekends, and weighted sleep duration (short: <7 hours or long: >9 hours) were determined. The circadian phenotype or chronotype were assessed by the reduced Horne & Östberg’s morningness-eveningness questionnaire. Blood pressure, weight, height, waist circumference, and blood biomarkers were measured. Three (3) cardiometabolic status scores were calculated. Hypertension (HTN) and metabolic syndrome (MS) were established. Results: Twenty one point three percent (21.3 %) of the study population presented a short weighted sleep duration and 16.7 % presented a long one. Twenty-eight point seven percent (28.7 %) showed a clearly morning chronotype, 38 % showed a moderately morning chronotype, 32.4 % showed no definite chronotype, 0.9 % showed a moderately evening chronotype, and there were no cases of clearly evening chronotype. Short sleep duration and morning chronotypes were more frequent in women > 40 years. The sleep duration was associated with marital status, occupation and ex-smoker status. The chronotypes were associated with postmenopause. The short sleep duration was associated with abdominal obesity and HTN, and elevation of gamma-glutamyltransferase and uric acid. The long sleep duration was associated with higher glycemia and transaminases. The clearly morning chronotype was associated with HTN, MS and presence of a number of MS components. The short sleep duration and the clearly morning chronotype predicted a high cardiometabolic risk. This association disappeared by adjusting the age and postmenopause status. Conclusions: The suboptimal sleep duration and the circadian phenotypes were associated with sociodemographic, clinical and cardiometabolic risk variables. The short sleep duration and the clearly morning chronotype predicted a high cardiometabolic risk.